Long‐term outcomes of endovenous laser ablation and conventional surgery for great saphenous varicose veins. Issue 13 (22nd August 2018) - Wallace, T.; El‐Sheikha, J.; Nandhra, S.; Leung, C.; Mohamed, A.; Harwood, A.; Smith, G.; Carradice, D.; Chetter, I.
Abstract : Background: Clinical guidelines recommend endovenous laser ablation (EVLA) over surgery based on short‐term evidence, yet there are few studies reporting mid‐ to long‐term outcomes. The aim of this study was to report the 5‐year outcomes from an RCT of surgery versus EVLA for treatment of symptomatic great saphenous varicose veins. Methods: Patients with symptomatic varicose veins due to great saphenous vein (GSV) incompetence were followed up 5 years after enrolment in a randomized trial of either surgery (saphenofemoral junction ligation, GSV strip to the knee and multiple avulsions of varicosities) or EVLA plus multiple avulsions. Outcomes included: clinical recurrence, defined as new varicose veins greater than 3 mm in diameter; Venous Clinical Severity Score (VCSS); quality of life measured by means of Short Form 36, EuroQol Five Dimensions (EQ‐5D™) and Aberdeen Varicose Vein Questionnaire (AVVQ); patient satisfaction; and duplex ultrasound examination (DUS) findings. Results: Some 218 of the 276 patients enrolled in the trial (79·0 per cent) were available for follow‐up. Clinical recurrence was more frequent following surgery than EVLA at 5 years (34·3 versus 20·9 per cent; P  = 0·010). Both groups demonstrated sustained significant improvements at 5 years over baseline in VCSS (surgery: median (i.q.r.) 1 (0–2) from 4 (3‐5), P  < 0·001; EVLA: 0 (0–1) from 4 (3‐5), P  < 0·001), AVVQ (surgery: 4·59 (0·56–9·78) from 13·69 (9·81–18·11), P  < 0·001; EVLA: 3·35 (0·17 to 6·55) from 12·73 (9·41–17·32), P  < 0·001) and EQ‐5D™ (surgery: 1·000 (0·796–1·000) from 0·859 (0·796–1·000), P  = 0·002; EVLA: 1·000 (0·796–1·000) from 0·808 (0·796–1·000), P  = 0·002). VCSS was better for EVLA than surgery at 5 years ( P  = 0·031). Technical success assessed by DUS remained high at 5 years (85·4 per cent for surgery and 93·2 per cent for EVLA; P  = 0·074). DUS‐detected anatomical patterns of recurrence differed between the groups. Conclusion: EVLA was more effective than surgery in preventing clinical recurrence 5 years after treatment of great saphenous varicose veins. Patient‐reported outcome measures were similar. Registration number: NCT00759434 (http://www.clinicaltrials.gov ). Abstract : Lower recurrence at 5 years after laser